The Impact of Foreign Direct Investment Inflows on the Economic Growth of Bangladesh. The Roles of Infrastructural Facilities - Mostafa, Md Showkat (My University, 2016)
Foreign direct investment (FDI) inflow has been a key concern for Bangladesh to obtain additional support for the economic development. The Government of Bangladesh continuously competing with other South Asian countries and putting more effort to increase the number of FDI inflows in the country. From the country’s perspective, the constant increasing rate of economic growth shows a positive outcome of FDI inflow. However, the country still not performing up to the mark to pull enough FDI inflows to its potential. Thus, this study discusses about the major determinants and factors affecting FDI inflows in Bangladesh. Among those determinants and factors, infrastructural facility is considered as the most important to affect FDI inflows. FDI inflow is fundamentally depending upon infrastructural facilities to achieve its desire success. Foreign investors take this issue very seriously because based on this they can measure their ease of doing business in the host country. Despite of providing a large market size, due to having weak and lack of infrastructural facilities, Bangladesh is facing trouble in drawing attention of the foreign investors. In order to make the infrastructural facilities happen, it is highly required to organize each of the systems under of it. The body of this study discussed about the weak infrastructures in Bangladesh such as transport and communication, power and energy, education system, and governance services. Improvement in one of these systems cannot provide valuable positive changes on FDI inflows. It requires improvement in all the weak systems to grasp multinational companies and attract foreign investors. On the basis of this research problem, research questions are established. Both qualitative and quantitative methods are used to answer the research questions. Furthermore, several theories have been applied to justify possible scenarios from the research problem. In addition, the history in between Bangladesh, trade liberalization, and FDI inflows is presented briefly.